2020
DOI: 10.1101/2020.05.21.20108746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What do we know about SARS-CoV-2 transmission? A systematic review and meta-analysis of the secondary attack rate, serial interval, and asymptomatic infection

Abstract: Background Current SARS-CoV-2 containment measures rely on the capacity to control person-to-person viral transmission. Effective prioritization of these measures can be determined by understanding SARS-CoV-2 transmission dynamics. We conducted a systematic review and meta-analyses of three parameters: (i) secondary attack rate (SAR) in various settings, (ii) clinical onset serial interval (SI), and (iii) the proportion of asymptomatic infection. Methods and Findings We searched PubMed, medRxiv, and bioRxiv d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 120 publications
3
36
1
Order By: Relevance
“…The quantity P(S 0 | test+) is a function of other parameters P(S 1 | untested), α, β, meaning its distribution is entirely determined by those three parameters. However, we considered estimates of P(S 0 | test +) to be more reliable than those of P(test + |S 1 ) and P(test + | S 0 ) because P(S 0 | test +) has been estimated in numerous published studies, including some with more representative sampling 1,2,4,[42][43][44][45] . Thus, we used Bayesian melding to incorporate both sources of information into a joint (melded) distribution on P(S 0 | test +) and P(S 1 | test +) = 1 -P(S 0 | test +) 46 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantity P(S 0 | test+) is a function of other parameters P(S 1 | untested), α, β, meaning its distribution is entirely determined by those three parameters. However, we considered estimates of P(S 0 | test +) to be more reliable than those of P(test + |S 1 ) and P(test + | S 0 ) because P(S 0 | test +) has been estimated in numerous published studies, including some with more representative sampling 1,2,4,[42][43][44][45] . Thus, we used Bayesian melding to incorporate both sources of information into a joint (melded) distribution on P(S 0 | test +) and P(S 1 | test +) = 1 -P(S 0 | test +) 46 .…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, it is possible that individuals who were asymptomatic at the time of testing developed symptoms later. A meta-analysis reported that 25.9% (95% CI: 18.8%, 33.1%) of individuals who tested positive were asymptomatic at the time of diagnosis (N = 25 studies) 45 , and a narrative review reported a similar range of estimates from 16 studies 44 . Though there were more studies to support this prior than for other priors, we chose not perform a meta-analysis to obtain the prior distribution due to limitations that affect the generalizability of the majority of these studies.…”
Section: Definition Of Distribution Of P(s 1 |Untestedmentioning
confidence: 98%
See 1 more Smart Citation
“…Since various studies have highlighted the existence of asymptomatic virus carriers, screening campaigns aimed at identifying and isolating these subjects could substantially contribute to the achievement of these objectives. Defining the prevalence of asymptomatic subjects, the fraction that later develop symptoms, their viral load and their transmission potential are still under investigations [10][11][12][13][14][15] . However, some mathematical modelling studies hypothesized that asymptomatic subjects can be the major responsible for COVID-19 transmission 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is now known that the course of infection includes an incubation pre-symptomatic period, during which the patients shows no sign of disease but are still potentially infectious (likely to a lesser degree), after which some individuals progress to a symptomatic state, while others remain asymptomatic, but still potentially infectious [8]. This behavior has important consequence on how we model COVID-19's epidemiology and plan countermeasures.…”
Section: Introductionmentioning
confidence: 99%